Blood Flow Separator Design In Passive Lab-On-Chip Device - Narayanamurthy, Vigneswaran; Maruthu Pandiyan, Sushmitha; Kiruba Sebatiny, Sebastin Solomon Kenned; Thenra, Jeyasri; M, Anisha; Kannan, Anusha devi (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Nowadays, most of the clinical analytical tests are performed by separating the blood particles and it is exclusively used to diagnose the diseases in the medical field. There are various techniques which can be done through separating the particles, yet there are ways to go further for making the separation of particles efficient. Therefore, an on-chip integrated microfluidic device is required for separating the blood particles. The particle separation can be achieved by using porosity method which comes under the filtration techniques. The designed device consists of an inlet and an outlet reservoir. The device has a top channel and bottom channel for the blood flow where the filters are placed at the middle. By this way of filtration, it can easily separate normal and abnormal blood particles. From the whole blood sample, the particles are trapped by using hydrodynamics trapping method. The passive device is designed by COMSOL Multiphysics software and design results are presented.